Cone-beam computed tomography – adding a new dimension to ERCP - Weigt, Jochen; Pech, Maciej; Kandulski, Arne; Malfertheiner, Peter (Endoscopy, 2015)
Six patients with biliary duct pathologies were investigated with three-dimensional endoscopic retrograde cholangiopancreatography (3D-ERCP). The technique of 3D-ERCP consists of c-arm rotation using a flat detector c-arm to acquire a complete set of images for 3 D visualization of the biliary system. Our case series demonstrates a high level of accuracy with regard to the diagnosis of stenosis and biliary leakage. In two patients the diagnosis obtained from conventional ERCP changed significantly after 3D-ERCP. From these early observations we conclude that 3D-ERCP enhances the diagnostic performance of ERCP in a subset of patients with biliary tract disease.